先化简,在求值:(x+根号xy)/(y+根号xy)+((根号xy)-y)/(x-根号xy),其中x=根号3+1,y=根号3-1先化简,再求值:(x+根号xy)/(y+根号xy)+((根号xy)-y)/(x-根号xy),其中x=根号3+1,y=根号3-1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 09:02:36
先化简,在求值:(x+根号xy)/(y+根号xy)+((根号xy)-y)/(x-根号xy),其中x=根号3+1,y=根号3-1先化简,再求值:(x+根号xy)/(y+根号xy)+((根号xy)-y)/(x-根号xy),其中x=根号3+1,y=根号3-1
先化简,在求值:(x+根号xy)/(y+根号xy)+((根号xy)-y)/(x-根号xy),其中x=根号3+1,y=根号3-1
先化简,再求值:(x+根号xy)/(y+根号xy)+((根号xy)-y)/(x-根号xy),其中x=根号3+1,y=根号3-1
先化简,在求值:(x+根号xy)/(y+根号xy)+((根号xy)-y)/(x-根号xy),其中x=根号3+1,y=根号3-1先化简,再求值:(x+根号xy)/(y+根号xy)+((根号xy)-y)/(x-根号xy),其中x=根号3+1,y=根号3-1
(x+根号xy)/(y+根号xy)+((根号xy)-y)/(x-根号xy),
=√x(√x+√y)/√y(√x+√y)+√y(√x-√y)/√x(√x-√y)
=√x/√y+√y/√x=(x+y)/√xy
x=√3+1 y=√3-1 ∴x+y=2√3 xy=2
∴(x+y)/√xy=2√3/2=√3
(x+√xy)/(y+√xy)+(√xy-y)/(x-√xy)
=[(x+√xy)×(x-√xy)+(√xy-y)×(y+√xy)]/[(y+√xy)×(x-√xy)]
=(x²-xy+xy-y²)/(xy+x√xy-y√xy-xy)
=(x²-y²)/[(x-y)√xy]
=(x-y)(x+y)/[(x-y)√xy]
全部展开
(x+√xy)/(y+√xy)+(√xy-y)/(x-√xy)
=[(x+√xy)×(x-√xy)+(√xy-y)×(y+√xy)]/[(y+√xy)×(x-√xy)]
=(x²-xy+xy-y²)/(xy+x√xy-y√xy-xy)
=(x²-y²)/[(x-y)√xy]
=(x-y)(x+y)/[(x-y)√xy]
=(x+y)/√xy
=(√3+1+√3-1)/√(√3+1)(√3-1)
=2√3/√2
=√6
收起
[x+√(xy)]/[y+√(xy)]+[(√(xy)-y]/[x-√(xy)]
=√x(√x+√y)/[√y(√y+√x)]+√y(√x-√y)/[√x(√x-√y)]
=√x/√y+√y/√x
=x/√(xy)+y/√(xy)
=(x+y)/√(xy)
=(√3+1+√3-1)/√[(√3+1)(√3-1)]
=2√3/2
=√3